2020
DOI: 10.1017/s0022149x20000462
|View full text |Cite
|
Sign up to set email alerts
|

Updated checklist of helminths found in terrestrial mammals of Argentine Patagonia

Abstract: Abstract The aim of the present study was to evaluate the state of knowledge about the helminthology of wild mammals in Argentine Patagonia and its link with the conservation of parasite species and biodiversity. To this end, the information included in the previously reported checklist of the helminths found in terrestrial wild mammals of Argentine Patagonia was completed and updated. The methodology used for the search was the same as that previously used, with slight modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 251 publications
(493 reference statements)
1
12
0
1
Order By: Relevance
“…For each case, this sediment was centrifuged at 1500 rpm for 5 min, washed and used to prepare 2 temporary slides. For parasitological identification, the exhaustive list of terrestrial mammal helminths of Patagonia (Fugassa, 2020), taxonomic descriptions of helminths and various handbooks (Soulsby, 1987;Miyazaki, 1991;Foreyt, 2001;Zajac and Conboy, 2012, among others) were used. The classification was performed following the higher-level classification system of Anderson (2000) and Anderson et al (2009) for the phylum Nematoda, Khalil et al (1994) and Kuchta et al (2008) for the class Cestoda, Gibson et al (2002), Jones et al (2005) and Bray et al (2008) for the subclass Digenea and Amin (2013) for the phylum Acantocephala.…”
Section: Methodsmentioning
confidence: 99%
“…For each case, this sediment was centrifuged at 1500 rpm for 5 min, washed and used to prepare 2 temporary slides. For parasitological identification, the exhaustive list of terrestrial mammal helminths of Patagonia (Fugassa, 2020), taxonomic descriptions of helminths and various handbooks (Soulsby, 1987;Miyazaki, 1991;Foreyt, 2001;Zajac and Conboy, 2012, among others) were used. The classification was performed following the higher-level classification system of Anderson (2000) and Anderson et al (2009) for the phylum Nematoda, Khalil et al (1994) and Kuchta et al (2008) for the class Cestoda, Gibson et al (2002), Jones et al (2005) and Bray et al (2008) for the subclass Digenea and Amin (2013) for the phylum Acantocephala.…”
Section: Methodsmentioning
confidence: 99%
“…quartus is reported for the first time from C . villosum (Santos and Gibson, 2015 ; Jiménez et al ., 2017 ; Fugassa, 2020 ), a bat species that occurs from southeastern Mexico to South America (Garbino et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This bat occurs from southeastern Gulf of Mexico to Guyana and Peru, but no previous records of helminths have been reported for it (Torres-Morales et al, 2014;Santos and Gibson, 2015;Jiménez et al, 2017). In addition, N. quartus is reported for the first time from C. villosum (Santos and Gibson, 2015;Jiménez et al, 2017;Fugassa, 2020), a bat species that occurs from southeastern Mexico to South America (Garbino et al, 2020).…”
Section: Helminth Fauna Of Collected Batsmentioning
confidence: 94%
“…Importantly, the invasion of free-living animals can also lead to the simultaneous invasion of their parasites, as well as to an increase in the prevalence of indigenous parasites for which they are potential hosts (Torchin et al 2003; Kelly et al 2009). For example, parasitological studies performed in guanacos during the last 40 years have shown a parasite richness made up of numerous helminths typical of domestic mammals (revised in Fugassa 2020). Thus, it is difficult to discern whether some of the species that currently parasitize SACs have a native or a foreign origin.…”
Section: Introductionmentioning
confidence: 99%